Le quartier antique des Bénédictins à Nîmes (Gard) Découvertes anciennes et fouilles 1966-1992 - Garmy, Pierre; Monteil, Martial (Documents d'archéologie française, 2000)
The results of the excavation, undertaken in Nîmes from 1966 to 1992, of the sites of the Marseillaise, the Villégiales des Bénédictins, the Hesperides and the Fontaine des Bénédictins, make it possible to follow the evolution of the Bénédictins district from the neolithic to the present day. Near a pre-roman oppidum, on the slopes of mount Cavalier, this area was occupied from the end of the sixth century BC, later finding itself at the heart of the old town after construction of the atywall during Augustus reign. No longer an urban area from the second century AD onwards, it remained rural until the eighteenth century.Organised according to a framework which respected the relief, with both water supply system and drainage, this district contained a group of houses whose plans, construction details, decoration and domestic finds are studied both individually and from a socio-economic point of view.